THE INFLUENCE OF INFLATION, EXCHANGE RATES, CAR AND NPF TO STABILITY OF ISLAMIC BANKS IN INDONESIA PERIOD 2015-2019 - L.P., Gumilang Budi; Kusnendi, Kusnendi; Utami, Suci Aprilliani (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2020)
This study aims to see the extent of the influence of the level of Inflation (CPI), Exchange Rate (kurs), Capital Adequacy Ratio (CAR) and Non Performing Financing (NPF) on the Stability of Islamic Banks in Indonesia Period 2015-2019. To support research, we use the Vector Error Correction Model (VECM) methodology. VECM test results show that in the short term the significant effect on the level of stability are Kurs and CAR, with the direction of a negative relationship (reducing the level of stability). Meanwhile, in the long term the significant effect on the level of stability are inflation and Kurs with the direction of a negative relationship (reducing the level of stability). From the results of this study it can be concluded that the macroeconomic variables significantly affect the stability of Islamic banking, therefore the government has an important role in controlling macroeconomic turmoil to maintain Islamic banking stability. Besides that, the internal variables of the banking sector are considered to have no significant effect partially, therefore it is necessary to conduct further research with a variety of internal factors in the banking industry to prove their effects on the stability of Islamic banking